(untitled) (Eurasian Journal of Philology Science and Education, 2022)
This article focuses on the term “linguoculturology”and “concept” which is aroused at the junction of cultural studies and linguistics. The connection of linguoculturology with linguistics is due to the fact that linguoculturology investigates phenomena at the interface of language, communication and culture, and uses linguistic methods, among others. However, while linguistics aims to learn more about language, including information on the connection between language and culture, linguoculturology uses linguistic facts to learn how culture is organised and functions Modern linguistics studies language for interpreting human culture. Linguistic and cultural studies reveal cultural symbols in the data of the national language, investigate its national-cultural agreement and identify its specific features. Also in modern linguistics, the linguocultural direction belongs to the field of general linguistics and has a particular scientific nature in relation to language and culture; its subject area is the sphere of interaction between culture and natural language. Linguoculturology as a direction, which deals with the analysis of the interaction between language and culture, language and consciousness, is the search for new research methods. This is explained by the fact that language is the key to the system of human thought, to the nature of the human psyche, it serves to characterise a nation. The tasks of linguoculturology include the study and description of the relationship between language and culture, language and ethnicity, language and national mentality. Therefore, at present, the study of the national language and national culture has led to a wide expansion of the field of linguistics, called linguoculturology.